The Economic Emergence of China: Strategic Policy Implications for Southeast Asia - Ng Beoy Kui (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2008)
The purpose of this paper is to analyze strategic policy implications arising from possible threats and opportunities in the face of the emergence of China as an economic powerhouse. The focus of the paper is not on the regional approach through mainly regional co-operations but more on policy strategies and responses at the national level. Depending on their degree of national economic development, economic structure and comparative advantage, eight strategic positionings have been identified. Of these eight positionings, direct competition is considered as an unwise move, considering China being endowed with relatively cheap labour resources. Together with its huge domestic market which can serve as a magnet for direct foreign investment, competition in attracting FDI can be a daunting task for most to the Southeast Asian countries. Instead, competition based on niche areas through branding, for instance provides a feasible alternative. The other alternative is to avoid direct competition by upgrading its economy, venturing into those areas where China has no comparative advantage as well as looking inward for sources of growth. Others may adopt 'connecting' strategies such as complementing or supplementing the Chinese economy by meeting China's increasing demand for natural resources or exploiting its huge domestic market. Still others may explore the possibilities of forging strategic alliance with China in the global market or playing the role of a middleman between China the West.
hdl:10398/7397
Keywords: 330; Globalisierung; Entwicklung; Auslandsinvestition; Wirtschaftswachstum; Wettbewerb; China; Südostasien